Straw interlayer improves sunflower root growth: Evidence from moisture and salt migration and the microbial community in saline-alkali soil - Mengmeng Chen; Guoli Wang; Yupeng Jing; Jie Zhou; Jiashen Song; Fangdi Chang; Ru Yu; Jing Wang; Weini Wang; Xia Sun; Hongyuan Zhang; Yuyi Li (Journal of Integrative Agriculture)
A straw interlayer added to soil can effectively reduce soil salinity effects on plant growth, however, the effects of soil moisture, salt and microbial community composition on plant growth under a straw interlayer are unclear. A rhizobox study was conducted to investigate the role of straw interlayer thickness on soil moisture, salt migration, microbial community composition, as well as root growth in sunflower. The study included four treatments: Control (no straw interlayer); S3 (straw interlayer of 3.0 cm); S5 (straw interlayer of 5.0 cm); S7 (straw interlayer of 7.0 cm). Straw interlayer treatments increased soil moisture by 8.2–11.0% after irrigation and decreased soil salt content after the bud stage in 0–40 cm soil. Total root length, total root surface area, average root diameter, total root volume and the number of root tips of sunflower plants were higher under straw interlayer treatments than in the control, and were the highest under the S5 treatment. This stimulated root growth was ascribed to the higher abundance of Chloroflexi and Verrucomicrobia bacteria in soil with a straw interlayer, which was increased by 55.7 and 54.7%, respectively, in the S5 treatment. Addition of a straw interlayer of 5 cm thickness is a practical and environmentally feasible approach for improving sunflower root growth in saline-alkali soil.